Geographic distribution of Cynomys mexicanus - Gonzalez-Uribe, Dino Ulises; García-Aranda, Mario Alberto; Heredia-Pineda, Feliciano; Uvalle-Sauceda, José Isidro (Ecosistemas y Recursos Agropecuarios, 2024)
The distribution and geographic range of Cynomys mexicanus was studied through geographic databases (GDB) and walking tours in the states of Coahuila, Nuevo León and San Luis Potosí, where active colonies (AC) of the species were located. An information search was conducted in the period 1985-2022 to identify AC GDB that were projected in Google Earth® to eliminate geographic inconsistencies. The records were checked in the field and another GDB was generated which was called current distribution (CD), fragmentation index were estimated of: interaction between AC (li), isolation (ri) and connectivity (ai). It was possible to obtain eight GDB, six of them free of geographical inconsistencies, the common thing was to lack the Datum. The CD area of AC was 231.20 km2, decreased 28.20% from 2004 (322 km2) and 11.73% compared to 2012 (284.22 km2). Through a principal components analysis (PCA) and multivariate discriminant analysis (MANOVA), the statistical relationships of the AC fragmentation index were evaluated, which showed that isolation (ri) and connectivity (ai) explained the relationship of AC in the three states where they are distributed.